Ответы и объяснения

2013-03-27T10:28:26+04:00

\left \{ {{x^2+3y=(x+1)^2+12} \atop {2x-5y=-17}} \right.

 

\left \{ {{x^2+3y=(x+1)^2+12} \atop {x=\frac{5y-17}{2}}} \right. 

 

подставляем x=\frac{5y-17}{2} в x^2+3y=(x+1)^2+12

 

(\frac{5y-17}{2})^2+3y=(\frac{5y-17}{2}+1)^2+12 

 

(\frac{5y-17}{2})^2+3y=(\frac{5y-17}{2})^2+(5y-17)+1+12 

 

3y=(5y-17)+13 

 

3y=5y-4 

 

2y=4

y=2

 

подставляем значение y в любое из уравнений системы и находим х

 

2x-5*2=-17

2x=-17+10

2x=-7

x=-3.5

 

\left \{ {{y=2} \atop {x=-3.5}} \right. 

Ответ: (-3,5;2)